Beyond Aro and the Ivory Tower: Thomas Adeoye Lambo and Contributions to Humanity - Ezekiel Oladele, Adeoti (Kashere Journal of Humanities, Management and Social Sciences, 2022)
After a brilliant career in Ibadan as a scholar, administrator and psychiatrist of world renown, Professor Thomas Adeoye Lambo became the Assistant Director General and later Deputy Director General of the World Health Organization (WHO) between 1971 and 1988. After his retirement, he served as proprietor and manager of the Lambo Health Foundation until 2004 when he passed on. This study examines critically his contributions to the general public health system in the world and humanitarian welfare services in his capacity as a notable WHO chieftain and chief executive officer of the Lambo Foundation Center. This work adopts historical narrative and analytical method of historical research. Findings reveal that the WHO is one avenue through which Lambo interacted with the world and where he faced enormous challenges, which he tackled professionally and efficiently. He recorded landmark achievements by focusing attention on neglected communicable diseases ravaging the Third World, ensured sustained funding and strengthened research in those areas. Thus, Lambo effectively changed the narrative of WHO on the deteriorating health conditions of the African people. Through his pet project, the Lambo Health Foundation, he also demonstrated his love for humanity by developing new and independent institutions for teaching, training and research in clinical medicine and all branches of basic biology and medicine, among others. He mentored promising scholars of Nigerian and African origin to undertake specialized overseas and post graduate training in medicine and psychiatry, thus boosting local capacity. His vision, resourcefulness, drive, diligence, integrity and statesmanship were deployed for the betterment of his nation.